2022
DOI: 10.1177/08258597211072946
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Radiotherapy for Esophageal and Gastric Cancer: Population-Based Patterns of Utilization and Outcomes in Ontario, Canada

Abstract: Objective Patients with incurable esophageal and gastric cancer may develop local symptoms for which palliative radiotherapy (PRT) may be considered. We sought to evaluate patterns in utilization and outcomes of patients receiving PRT for incurable esophageal and gastric cancer in Ontario, Canada using health administrative data. Methods Linked health administrative databases were used to identify patients receiving PRT for incurable esophageal and gastric cancer. Primary outcomes were utilization and delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Additionally, it correlates with significantly lower risk of toxicity, better pain control and equivalent relief of moderate to severe dysphagia [ 18 ]. Although intraluminal brachytherapy proved to be effective [ 14 ], it is more invasive and less widely implemented than external beam RT [ 9 , 19 , 20 ], with comparable efficacy [ 21 ]. Furthermore, patient-reported outcomes seem to favour external beam RT [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it correlates with significantly lower risk of toxicity, better pain control and equivalent relief of moderate to severe dysphagia [ 18 ]. Although intraluminal brachytherapy proved to be effective [ 14 ], it is more invasive and less widely implemented than external beam RT [ 9 , 19 , 20 ], with comparable efficacy [ 21 ]. Furthermore, patient-reported outcomes seem to favour external beam RT [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, this population, which was excluded from prospective studies, is worthy of specific attention, and further studies are needed to investigate the efficacy of immunotherapy. Previous studies have confirmed that palliative radiotherapy plays an important role in relieving bleeding, obstruction, and pain and in improving the quality of life of patients with advanced gastric cancer; however, the relationship between palliative radiotherapy and survival is unclear ( 23 25 ). A total of 59 patients with advanced gastric cancer who received palliative radiotherapy during the course of the disease were included in this study, and the corresponding results showed that palliative radiotherapy improved their OS.…”
Section: Discussionmentioning
confidence: 99%